2017
DOI: 10.4103/sni.sni_228_17
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of 229 surgically treated patients with brain metastases: Prognostic factors, outcome and comparison of recursive partitioning analysis and diagnosis-specific graded prognostic assessment

Abstract: Background:Metastases are the most frequent tumors in the brain. Most often used scoring systems to predict the outcome are the RPA (Recursive Partitioning Analysis) classification and the DS-GPA (Diagnosis-Specific Graded Prognostic Assessment) score. The goal of our study was to determine prognostic factors which influence outcome in patients who undergo surgery for brain metastases and to compare different outcome scores.Methods:Two hundred and twenty-nine patients who underwent surgery for brain metastases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 68 publications
5
7
0
Order By: Relevance
“…The Radiation Therapy Oncology Group (RTOG) developed an RPA classification system in which patients are statistically classified by KPS score, age, and status of extracranial disease . In this study, patients were also classified into three classes according to the RPA classification: the median survival rates were 13.4 (class I), 9.1 (class II), and 2.4 (class III) months ( P < 0.001), similar to the results of previous reports . BM patients could also benefit from better KPS scores.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The Radiation Therapy Oncology Group (RTOG) developed an RPA classification system in which patients are statistically classified by KPS score, age, and status of extracranial disease . In this study, patients were also classified into three classes according to the RPA classification: the median survival rates were 13.4 (class I), 9.1 (class II), and 2.4 (class III) months ( P < 0.001), similar to the results of previous reports . BM patients could also benefit from better KPS scores.…”
Section: Discussionsupporting
confidence: 82%
“…However, Pojskic et al . concluded that the mean survival of patients with multiple BM was not statistically different from that of patients with a single metastasis . Similarly, Hong et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies have shown that the average survival of patients with multiple BMs is not statistically different from that of patients with single metastasis [164].…”
Section: Prognostic Factors Of Nsclc Cns Metastasismentioning
confidence: 91%